2016
DOI: 10.1530/jme-16-0138
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone augments cell susceptibility to HIV-1 and HIV-1/HSV-2 co-infections

Abstract: In human immunodeficiency virus type 1 (HIV-1)-infected women, oral or injectable progesterone containing contraceptive pills may enhance HIV-1 acquisition in vivo, and the mechanism by which this occurs is not fully understood. In developing countries, Herpes simplex virus type-2 (HSV-2) co-infection has been shown to be a risk for increase of HIV-1 acquisition and, if co-infected women use progesterone pills, infections may increase several fold. In this study, we used an in vitro cell culture system to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(54 reference statements)
0
11
1
Order By: Relevance
“…Studies in ovariectomized mouse models have indicated that progesterone treatment increases the susceptibility of females to genital HSV-2 infection whereas estrogen treatment helps clear the infection rapidly. Interestingly, combined treatment of estrogen and progesterone in ovariectomized mice depicted increases the infection spread accompanied by persistent inflammation and neutrophil infiltration (125, 126). Although studies do not directly indicate the organizational effect but effect of estrogen and progesterone in ovariectomized animals suggests effect of sex hormones in HSV-2 infection.…”
Section: Dna Virus Members Of the Herpesviridae Familymentioning
confidence: 99%
“…Studies in ovariectomized mouse models have indicated that progesterone treatment increases the susceptibility of females to genital HSV-2 infection whereas estrogen treatment helps clear the infection rapidly. Interestingly, combined treatment of estrogen and progesterone in ovariectomized mice depicted increases the infection spread accompanied by persistent inflammation and neutrophil infiltration (125, 126). Although studies do not directly indicate the organizational effect but effect of estrogen and progesterone in ovariectomized animals suggests effect of sex hormones in HSV-2 infection.…”
Section: Dna Virus Members Of the Herpesviridae Familymentioning
confidence: 99%
“…HIV replication is dependent on the host transcriptional machinery and many of these host factors are determinants of cell tropism and host range of HIV and could positively or negatively regulate HIV replication. Several studies have implicated steroid hormones estrogen and progesterone in influencing HIV transmission and modulating HIV replication [ 6 14 ]. Reports indicate that the use of progesterone based injectable hormonal contraceptives is associated with an immunosuppressive female genital tract environment that could influence susceptibility to HIV infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In women infected with HIV-1, contraceptive pills containing progesterone increase the susceptibility to the infection in vivo. It has also been observed that the treatment with progesterone increases the replication of HIV-1 in cells [40]. The reduced expression of PR and a high viral load result in a precarious pregnancy in hepatitis E [41].…”
Section: Discussionmentioning
confidence: 99%